MAPPING MACROPLASTIC DISTRIBUTION IN JAKARTA BAY WITH NUMERICAL MODELING METHODS IN THE WEST AND EAST MUSON - Siti Noorrahmah, Ajeng
Plastic garbage is a major problem against marine pollution in Jakarta Bay. Macroplastic is one type of plastic garbage that can be seen with the eyes due to its large size. Its mild nature makes this macroplastic garbage float following the surface currents and the partially drowned macroplastics. Cisadane River is one of the rivers of plastic garbage donors to the Bay of Jakarta. There are many plastic garbage piling on the coast around the estuary of Cisadane River. Macroplastic garbage derived from the Cisadane River will follow the current sea level surrounding it caused by factors such as wind, tides, water depth, and river water discharge. This research aims to perform the mapping of macroplastic garbage distribution in the Bay of Jakarta that originated from the Cisadane River during the western monsoon and east monsoon. The method is by numerical modeling using the software Delft3D. The results obtained at the time of the eastern monsoon show that the surface currents bring more garbage to the west with dominating winds coming from the southeast. At the end of the simulation of macroplastic concentrations at an observation point 3 (west) at the time of the eastern monsoon of 1.5x10-6 kg/m3. At the time of the eastern monsoon, macroplastic garbage moved 29.76 km to the northwest of the mouth of the Cisadane River. While the results obtained at the time of the west monsoon shows that the surface currents carry more macroplastic garbage eastwards with the dominating winds coming from the northwest. At the end of the simulation of macroplastic concentrations at an observation point 2 (east) of 2.7x10-5 kg/m3. At the time of the West monsoon, Macroplastic Garbage moved 52.94 km eastwards from the estuary of Cisadane River.